La nueva gramática, el “dernier cri” de la RAE - Miranda, Luis (2012)
In this article a critical analysis is made of the “Nueva Gramática de la Lengua Española” recently published by the Real Academia de la Lengua Española, considering not only the unjustified emphasis on the “new” aspects but also the inadequacies shown from a scientific perspective.